Effect of wearing a helmet on the occurrence of head injuries in motorcycle riders in Benin: a case-control study - Bella Hounkpe Dos Santos; Yolaine Glele Ahanhanzo; Alphonse Kpozehouen; Donatien Daddah; Emmanuel Lagarde; Yves Coppieters (BMC, 2021)
Abstract Background In Benin, motorcycles are the main means of transport for road users and are involved in more than half of crashes. This study aims to determine the effect of wearing a helmet on reducing head injuries in road crashes in Benin. Methods This case-control study took place in 2020 and focused on road trauma victims. The sample, consisting of 242 cases (trauma victims with head injuries) for 484 controls (without head injuries), was drawn from a database of traffic crash victims recruited from five hospitals across the country from July 2019 to January 2020. Four groups of independent variables were studied: socio-demographic and economic variables, history, behavioural variables including helmet use and road-related and environmental variables. To assess the shape of the association between the independent variables and the dependent variable, a descending step-by-step binary logistic regression model was performed using an explanatory approach. Results Fewer of the subjects with a head injury were wearing a helmet at the time of the crash 69.8% (95% CI = 63.6-75.6) compared to those without a head injury 90.3% (95% CI = 87.3-92.8). Adjusting for the other variables, subjects not wearing helmets were at greater risk of head injuries (OR = 3.8, 95% CI (2.5-5.7)); the head injury rating was 1.9 (95% CI = 1.2-3.3) times higher in subjects who were fatigued during the crash than among those who were not and 2.0 (95% CI = 1.2-3.3) times higher in subjects with no medical history. Conclusion Failure to wear a helmet exposes motorcyclists to the risk of head injuries during crashes. It is important to increase awareness and better target such initiatives at the subjects most at risk.